Determining factors in Romanian consumer behavior on the nuts market (nuts, cashews, almonds, pistachios) - Ruxandra-Eugenia Pop (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
Within the internal research plan of the Research Institute for Agrarian Economy and Rural Development, the project entitled "Marketing studies for sustainable agri-food products and analysis of consumption behavior, in the objectives context of the European strategy From farm to Fork (From farm to consumer )". Starting from the objectives of the strategy mentioned in the title of the project, in the first phase, we identified 4 groups of agri-food products for which marketing studies will be carried out, respectively: nuts, fruits, vegetables and whole grains. The present work presents the main results obtained following the analysis methodology used, to outline the profile of consumers of nuts in Romania, as well as a form of validation or not of research hypotheses, using the SPSS program, in order to calculate reference parameters for studying the synergies between the independent and dependent variables under research, such as the chi-square test or the contingency coefficient.
Keywords: M31; C12; 330; consumer behavior; quantitative research; chi-square test; contingency coefficient; nut market